2018
DOI: 10.1088/1361-6463/aab590
|View full text |Cite
|
Sign up to set email alerts
|

Discharge runaway in high power impulse magnetron sputtering of carbon: the effect of gas pressure, composition and target peak voltage

Abstract: Pressure and target voltage driven discharge runaway from low to high discharge current density regimes in high power impulse magnetron sputtering of carbon is investigated. The main purpose is to provide a meaningful insight of the discharge dynamics, with the ultimate goal to establish a correlation between discharge properties and process parameters to control the film growth. This is achieved by examining a wide range of pressures (2–20 mTorr) and target voltages (700–850 V) and measuring ion saturation cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…In the reported process, change of the processing atmosphere by addition of either Ne or of C 2 H 2 had a similar effect on the electrical behaviour of HiPIMS pulses. In both cases, an increase of the peak current at a constant discharge voltage was observed, in agreement with earlier reports [21]. The probability of arc ignition increased proportionally with the discharge current, as it was shown in [29], due to the creation of hot spots on the target that provided the seeds for arc formation.…”
Section: Process Descriptionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the reported process, change of the processing atmosphere by addition of either Ne or of C 2 H 2 had a similar effect on the electrical behaviour of HiPIMS pulses. In both cases, an increase of the peak current at a constant discharge voltage was observed, in agreement with earlier reports [21]. The probability of arc ignition increased proportionally with the discharge current, as it was shown in [29], due to the creation of hot spots on the target that provided the seeds for arc formation.…”
Section: Process Descriptionsupporting
confidence: 92%
“…When comparing different process conditions it is very common to use the average power of the discharge as a constant parameter. In the case of HiPIMS on the other hand, it was previously shown that the peak current is the key parameter governing the sputtering regime and the ionization degree of the sputtered species [21,30]. We discuss therefore in the present paper, the use of the peak current as the main control parameter, to compare different deposition processes.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations